Relationship between perceived readiness to run and physiological variables during repeated 2000 m bouts in middle-distance runners - Karu, T.; Nurmekivi, A.; Lemberg, H.; Pihl, E.; Jurimae, T. (Scandinavian Journal of Medicine & Science in Sports, 2000)
The aim of this study was to investigate how heart rate (HR) and blood lactate (LA) concentrations are associated with perceived readiness ratings (PRR) to begin a new run during recovery after four different intensity steady-state 2000 m runs in college-level male middle-distance runners (n=15). A typical 4x2000 m run test with stepwise increasing speed was used on the indoor track (150 m lap). A new PRR scale was administered at each minute of recovery. The scale ranges from 1 to 5 points (from "not at all ready to begin" to "completely ready to begin"). Blood LA concentrations were measured immediately after runs and in the 3rd min of recovery after the first and second runs. In case of the third and fourth runs, blood LA was measured immediately after the runs and in the 3rd and 6th min of recovery. HR was recorded at the end of every minute of recovery. Highly significant inverse relationships were revealed between PRR, blood LA concentrations and HR during recovery (r>0.9 as a rule). After the third and the fourth 2000 m runs, where intensity was higher than LA threshold, PRR increased during 6 min up to 4.8+/-0.4 and 4.5+/-0.6, respectively, while HR fell below 120 beats x min(-1). However, blood LA concentration remained high. The reliability of the new PRR scale (tested on four runners), during recovery was very high (r=0.98). These results suggest that the PRR scale can be used by runners to determine the optimal duration of resting intervals between runs. Scand J Med Sci Sports 2000 Feb;10(1):33-6